2009
DOI: 10.1073/pnas.0805801106
|View full text |Cite
|
Sign up to set email alerts
|

Global warming-enhanced stratification and mass mortality events in the Mediterranean

Abstract: Summer conditions in the Mediterranean Sea are characterized by high temperatures and low food availability. This leads to ''summer dormancy'' in many benthic suspension feeders due to energetic constraints. Analysis of the most recent 33-year temperature time series demonstrated enhanced stratification due to global warming, which produced a Ϸ40% lengthening of summer conditions. Many biological processes are expected to be affected by this trend, culminating in such events as mass mortality of invertebrates.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
292
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 346 publications
(303 citation statements)
references
References 37 publications
9
292
1
1
Order By: Relevance
“…The occurrence of entire dead colonies in situ, without evident ruptures of branches, excludes, in fact, mechanical injuries, such as those produced by fishing activities. Neither can the mortality simply be attributed to pollution or thermal anomalies related to global changes (Cerrano et al 2000;Coma et al 2009;Garrabou et al 2009), owing to the offshore location of the site and the depth at which is situated.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of entire dead colonies in situ, without evident ruptures of branches, excludes, in fact, mechanical injuries, such as those produced by fishing activities. Neither can the mortality simply be attributed to pollution or thermal anomalies related to global changes (Cerrano et al 2000;Coma et al 2009;Garrabou et al 2009), owing to the offshore location of the site and the depth at which is situated.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the tropical eastern Atlantic biota, which evolved and still flourishes under a regime of high planktonic productivity thanks to seasonal upwelling or extensive input of land-based nutrients by rivers, the IWP biota in the Red Sea comes from a generally oligotrophic regime. The eastern parts of the Mediterranean Sea closest to the Suez Canal, through which Red Sea species are entering the Mediterranean, are becoming both warmer and more oligotrophic (Coma et al, 2009;Por, 2010) owing to the construction of the Aswan Dam on the Nile River in Egypt, which effectively eliminated a major source of terrestrial nutrients.…”
Section: Controls On Patterns Of Invasionmentioning
confidence: 99%
“…Bottom-water hypoxia in lakes is detrimental not only for the biota that would normally inhabit oxic aquatic and benthic environments but also facilitates biogeochemical reactions that generate methane and further mobilize pollutants from previously accumulated sediment, including P (26)(27)(28). Hypoxia can develop naturally, but is more often the result of (i) cultural eutrophication, which enhances biomass production and, ultimately, its decomposition through microbial oxygen respiration (29)(30)(31), and (ii) rising mean temperatures, which decrease oxygen solubility in water (32), stimulate microbial oxygen respiration (30), and/or strengthen thermal stratification (33,34). Among these forcing mechanisms, recent paleolimnological studies identified excess P availability, and not climate, as the main driver for the onset of lacustrine hypoxia during the Anthropocene (17,35).…”
mentioning
confidence: 99%